WOMEN CONTESTATION IN CHOPIN’S THE AWAKENING - Dewi Saraswati Angelin; Lusia Kristiasih Dwi Purnomosasi (English Teaching Journal : A Journal of English Literature, Language and Education, 2016)
This study aims at describing the depiction of four women in Creole community which is applied as the contestation in “The Awakening” and describing the reasons of Creole women’s character contestation which related to particular purpose in that time. The writer uses the descriptive qualitative method as research design. The data is collected by using documentation. The data sources in this research are divided into two parts, primary and secondary. The primary data is novel of The Awakening. The secondary data is taken from the history of Creole society in Louisiana, journals, and the other sources from the website as the information. The base of this research is focused on Pierre Bourdieu’s concept. This concept is used to discover the problem formulation through the sociologycal view which influences the way of thinking from four Creole women. The result of this research are a) the depiction of three women reveal that women can support economic as businesswomen and even artist. Meanwhile, the other one is submissive and worship to husband due to keep the balance in the household. b) the reasons of three women reveal that the men’s authority is not important due to their basic background that support their economic through their proficiency as their manifestation to exist in the society. Meanwhile, the other one relies on the man to support her economic and a man as symbolic power. Based on the finding, the distinctive ideology as genetic structuralism which is connected to economic , politic and social background influence  their way of thinking to get the opportunity.